Malaysian coffee products : a rebranding of Kopiesatu as a case study / Muhammad Farhan Mohd Abas - Mohd Abas, Muhammad Farhan (Faculty of Art and Design, 2013)
Coffee is one of the most popular beverages in the world. From the Free Dictionary.com, coffee means a beverages consisting of an infusion, filtration, or stewing a seed of coffee tree to make coffee drinks. Coffee beverages also can gives a lot of nutrition, one of it are it gives us energy to stay awake. Figure 1.1 shows the images of coffee bean. According to the 2010 edition of Stastistical Report coffee, these drinks are behind much petroleum as the hottest commodity in the business world, whichis about 400 billion cups consumed every year. The favorite of these beverage were shared by all people of all nation and cultures. There are 3 types of coffee which are Arabica, Liberica and Robusta. In coffee drinks, there are a few types of coffee drinks such as Cappuccino, Latte, Macchiato, Espresso, Mocha and etc.